Controle e estimulação de crescimento folicular em doadoras da raça holandesa para a produção in vitro de embriões - Ifran, Aderson Maurício [UNESP] (2014)
Holstein cows, bred in temperate to hot climate have low efficiency on the number, quality and oocyte competence for in vitro production of embryos, compared to Zebu breeds. On the other hand the control of follicular wave and stimulation with exogenous FSH can increase the number and improve the quality and oocyte competence for embryo production. With the comparative goal seven heifers, seven non-lactating cows and seven lactating cows were used in a complete crossover were subjected to four treatments: T1 - Follicular Aspiration randomly at any time of the estrous cycle; T2 - Follicular Aspiration two days after removal of the dominant follicle; T3 - Follicular Aspiration 24 hours after removal of the dominant follicle and stimulation with single dose of FSH (100 IU to 200 IU for heifers and non-lactating cows or lactating) twenty four hours before follicular aspiration; T4 - Follicular Aspiration after stimulation and induction of the LH surge (progestagen implant insertion, aspiration of the dominant follicle and FSH stimulation at a dose of 250 IU to 500 IU for heifers and non-lactating and lactating cows, subdivided in 8 decreasing doses, induce luteolysis and removal of the implant 36 hours before of the GnRH and follicular aspiration 24 hours after GnRH administration). No statistical difference between treatments (P>0.05) was evaluated oocyte retrieval was observed, however category heifers achieved better results and statistical differences (P<0.05) compared with lactating cows and non-lactating, although no statistical difference between the categories of non-lactating cows and lactating cows was observed. When the viable oocytes were evaluated, the grade of heifers showed better results and significant difference (P <0.05) compared with lactating and non-lactating cows, and no significant difference was observed between non-lactating cows and lactating cows (P>0.05). In relation to treatments, treatment 1 (T1) differed ...